Sickle cell trait associated with sudden death in competitive athletes - Harris, K. M.; Haas, T. S.; Eichner, E. R.; Maron, B. J. (The American Journal of Cardiology, 2012)
Sickle cell trait (SCT; hemoglobin AS) occurs in 8% of African Americans and although typically benign has been associated with sudden death in military recruits during intense physical activity. However, the role of SCT in the deaths of trained athletes is less well documented or acknowledged. The 31-year United States Sudden Death in Athletes Registry was interrogated to determine the frequency, epidemiology, and clinical profile of SCT-related death in a large population of competitive athletes. Of 2,462 athlete deaths, 23 (0.9% overall, 3.3% of African Americans) occurred in association with SCT: ages 12 to 22 years, 21 male (91%), and all African Americans. SCT diagnosis was made by solubility testing (n = 13) and/or hemoglobin electrophoresis (n = 16). Most victims competed in college (n = 17) and in football (n = 19). Of 271 African American football deaths in the registry, 7% (1 in 14) were known to be associated with SCT. Each athlete experienced distinctive noninstantaneous collapse with gradual deterioration over several minutes associated with vigorous or exhaustive physical exertion, usually during conditioning drills (n = 22) and typically early in the training season. Ambient temperatures were =80°F in 20 patients (87%), with most events in southern or border states during the summer and autumn (n = 17 [74%]). In conclusion, SCT can be associated with largely unpredictable sudden collapse and death and apparent predilection for African American college football players during conditioning. Understanding the risks, mechanisms, and event triggers of SCT may allow lifesaving alterations in training methods to be implemented.